CONTINUITY OF CARE FOR MIDWIFERY FOR SECON-DEGREE LACERACY OF THE BRITH WAY IN NY. N THE FRISKAH NOVITA PRIMARY CLINIC MEDAN LABUHAN DISTRICT MEDAN CITY NORTH SUMATRA IN 2025 - Mastari Br Juntak; Sinaga, Rosmani; Ginting, Siska Suci Triana; Anindhitya, Muhammad Riezky; Anindhitya, Safriani Loi; Silitonga, Yuni; Wati , Esra (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Perineal rupture is a perineal tear that occurs when a baby is born either spontaneously or with the use of tools or actions. Perineal tears generally occur in the midline and can be extensive if the fetal head is born too quickly. Perineal tears occur in almost all primiparas and are not uncommon in subsequent deliveries. Perineal factors are influenced by several factors, namely maternal factors, fetal factors and assisting factors.(Nainggolan.et.2020) Determining continuous midwifery care (Continuity Of Care) for Mrs. N with a second-degree birth canal at the Friskah Novita Pratam Clinic, Medan Labuhan District, North Sumatra in 2025. This research design uses a descriptive method, especially through a case study approach, conducting research by observing and caring for a 35-year-old woman during pregnancy, childbirth, and postpartum, as well as during family planning. (Nilan Sari et al. 2025) During Mrs. N's pregnancy. N, 24 years old, G1P0A0, with a gestational age of 28 weeks and 3 days based on HPHT April 11, 2024 days or 40 weeks from the first day of the last menstruation. Continuous care Contuinity Of Care used as a final assignment report for midwifery students is very helpful in understanding the process of pregnancy, childbirth, postpartum, newborns and family planning, especially for Mrs. N during the third trimester of pregnancy which began on October 27, 2024 until February 16, 2025 and the author conducted Contuinity Of Care guidance with the aim of successful Contuinity Of Care care.